CULTURAL DEVELOPMENT AND ITS IMPACT ON YOUNG PEOPLE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article is devoted to the study of the influence of culture on the youth of Asia in the context of globalization and technological progress. Traditional values, the influence of modern technologies, as well as the issues of preserving national identity among young people are considered.